Fast pyrolysis of hot-water-extracted and soda-AQ-delignified okra (Abelmoschus esculentus) and miscanthus (miscanthus x giganteus) stalks by Py-GC/MS. (November 2018) - Ghalibaf, Maryam; Ullah, Saleem; Alén, Raimo
Abstract: The thermochemical behavior of various samples of okra ( Abelmoschus esculentus ) and miscanthus ( Miscanthus x giganteus ) stalks (initial, hot-water-extracted, and those from sulfur-free delignification) were studied by pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS). In all cases, major GC-amenable condensable products were measured semi-quantitatively and classified into several product groups. The formation of these product groups from different feedstock samples with varying mass portions of their structural constituents (carbohydrates and lignin) was investigated at 500 °C and 700 °C with a residence time of 5 s and 20 s. The main product groups were aliphatic compounds, such as lactone, furan, and cyclopentenone derivatives from carbohydrates (mainly hemicelluloses) and aromatic compounds, such as guaiacol, phenol, and syringol derivatives from lignin. Additionally, the formation of aliphatic and aromatic products (e.g., the ratio of aliphatic compounds to aromatic compounds) was found to be characteristically dependent on feedstock composition and pyrolysis conditions. This kind of approach is of practical importance concerning efforts not only to uncover new integrated biorefinery possibilities to manufacture value-added products but also to develop rapid characterization tools for lignocellulosics. Highlights: Solid organic fractions from hot-water-extraction of targeted non-wood feedstocks were pyrolyzed. Fast pyrolysis has been utilized in the integrated biorefinery concept. The ratio aliphatic/aromatic pyrolysis compounds characteristically depends on feedstock composition and pyrolysis conditions. A basis of a rapid characterization method for lignocellulosics has been developed.